Peninjauan Pemanfaatan Ruang Dalam Mendukung Keselamatan Operasi Penerbangan Bandar Udara Budiarto Curug (Studi Kasus : Kecamatan Legok) - Dwi Setiyo Oktavianto; R. Sihadi D. Wihardjo (Magister Kajian Pembangunan Perkotaan dan Wilayah, 2024)
The increase in the number of flights is a complex phenomenon and has far-reaching impacts. It is important to manage this growth wisely, taking into account economic, environmental and security aspects, and ensuring that the right infrastructure and regulations are in place to support sustainable growth. This research aims to serve as a reference in fulfilling the requirements for appropriate space utilization in aviation operations safety areas. This research uses a qualitative descriptive approach. The analysis used is an analysis of space utilization in Legok sub-district and the area of possible accident hazards at Budiarto Airport, an analysis of the requirements for space utilization in the aviation operations safety area at Budiarto Airport in Legok sub-district and an analysis of the implementation of control in the use of space in the aviation operations safety area. Based on the results of the analysis of the Flight Operations Safety Area at Budiarto Airport in Legok District, an Airport Area zone has not been determined in the Tangerang Regency Regional Spatial Plan and there are inconsistencies in several buildings which could disrupt the safety of flight operations